The Thrity-Seventh Asilomar Conference on Signals, Systems &Amp; Computers, 2003
DOI: 10.1109/acssc.2003.1292044
|View full text |Cite
|
Sign up to set email alerts
|

An FPGA based rapid prototyping platform for MIMO systems

Abstract: Multiple input multiple output (MIMO) techniques hold the potential of dramatically increasing the data rates and spectral efficiency of wireless communications systems. Even with extensive research on the design of transmission and reception algorithms, little is known as to how much of the predicted gains are actually achievable on real wireless channels. In this paper, we present a MIMO testbed which enables the rapid prototyping of MIMO transceivers for wideband channels. Such prototypes provide experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
1

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 6 publications
(9 reference statements)
0
40
1
Order By: Relevance
“…Other examples of this type of platforms can be found in (19,20,26,27,28,29,30,31,32,33,34). If the features of the implemented MIMO platform are compared with the others found in the testbeds cited, it can be concluded that:…”
Section: Rf Modulesmentioning
confidence: 99%
“…Other examples of this type of platforms can be found in (19,20,26,27,28,29,30,31,32,33,34). If the features of the implemented MIMO platform are compared with the others found in the testbeds cited, it can be concluded that:…”
Section: Rf Modulesmentioning
confidence: 99%
“…This is made possible by advances at all levels of the simulator platforms [2]. With continuing increase of the Field Programmable Gate Array (FPGA) capacity, entire baseband systems can be mapped onto faster FPGAs for more efficient prototyping and testing [3]. Some MIMO hardware simulators are proposed by industrial companies like Spirent [4], Azimuth (ACE), Elektrobit (Propsim F8) [5], but they are quite expensive and they do not cover all types of environment.…”
Section: Introductionmentioning
confidence: 99%
“…First, majority of the prototypes reported were specifically designed for channel measurements [7,8,9,10,11,12,13,14,15,16] to study the improvement in MIMO channel capacities and effect of correlation between the antennas to verify simulation and analytical results. The second type of prototypes developed and showcased the requirements for implementing different MIMO algorithms in real time [17,18]. The VT-STAR system was built to allow both channel measurements as well as to demonstrate real-time and reconfigurable implementation aspects on the same DSP platform through software radio concepts.…”
Section: Introductionmentioning
confidence: 99%
“…A 3 × 3 broadband 20 MHz V-BLAST-based MIMO-OFDM prototype was developed for 802.11a standard in [16], where digital downconversion and signal conditioning were implemented on FPGA boards and the signal processing was done offline on collected data. A simple Alamouti scheme using with QPSK modulation for 2 × 2 STBC transmission was prototyped on FPGA boards [17] and verified on a wireless channel emulator (rather thana real-time over-the-air experimentation). The authors in [18] presented three types of MIMO testbeds developed at UCLA, the first two of which were based on offline processing while the remaining one was implemented on ASIC chips to provide real-time operation.…”
Section: Introductionmentioning
confidence: 99%